Komunikasi Pemasaran dalam meningkatkan Penjualan pada Toko Outfit Branded Store (OBS) - Anggita Hayatin Nufus; Siti Nursanti, Tri Susanto (Economic Reviews Journal, 2026)
The development of information technology and the increasing use of digital media have encouraged businesses to implement effective marketing communication strategies to increase sales. Outfit Branded Store (OBS) is a fashion retailer that sells branded clothing at affordable prices and utilizes various marketing communication channels in its operations. This study aims to determine the marketing communication strategies implemented by Outfit Branded Store (OBS) to increase sales, including advertising, personal selling, sales promotion, public relations and publicity, and direct marketing. This study used a qualitative descriptive method with data collection techniques including interviews, observation, and documentation. Informants in this study consisted of the store owner, employees, and customers of Outfit Branded Store (OBS). Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the marketing communication strategies implemented by Outfit Branded Store (OBS) have been quite effective in increasing sales. Advertising is carried out through social media such as Instagram, TikTok, and Facebook, as well as conventional media such as brochures and banners. Face-to-face sales are conducted by providing friendly service and comprehensive product information to customers. Sales promotions are conducted through discounts, vouchers, gifts, and special promotional programs. Public relations and publicity are built through good service and maintaining customer satisfaction, thus creating a positive store image. Meanwhile, direct marketing is conducted through personal communication with customers using social media and instant messaging applications. The implementation of various marketing communication strategies can increase market reach, attract consumer interest, build customer loyalty, and contribute to increased sales at the Outfit Branded Store (OBS).